Runoff erosion in Portugal: A broad overview - Carvalho, Mário (2013)
The Mediterranean conditions prevailing in Portugal are imposing several constrains to sustainable arable farming production. In this presentation it is discussed the role of conservation agriculture, namely no-till and crop residues management, as means to overcome some of the main problems using field experiments carried out in the Southern regions of Portugal. Long term field experiments are showing that conservation agriculture can control soil erosion and improve several soil properties like organic carbon, aggregates stability, continuous biological porosity and saturated hydraulic conductivity. As a consequence crop yields can be significantly increased and, at the same time, the amount of fertilizers can be reduced. Another important benefit is the better soil bearing capacity, that together with the drainage, improves soil trafficability under no-till. This allows a timely application of herbicides and fertilizers which offers the opportunity for further improvements of the efficient use of expensive production factors. The combine effect of all this benefits greatly enhances the sustainability of the arable cropping systems under Mediterranean conditions.